SÍNTESE E CARACTERIZAÇÃO DE CuO E α - MoO3 APLICADOS COMO SENSORES ELETROQUÍMICOS PARA A DETECÇÃO DE DISRUPTORES ENDÓCRINOS - ANTONIAZZI, CRISTIANE (2018)
This work describes the synthesis and characterization of copper copper (CuO) and molybdenum trioxide (MoO3) and development of modified carbon paste electrodes for determination of endocrine disrupters. CuO was applied as a sensor for determinatiion of 17β- estradiol (E2) and MoO3 for bisphenol A (BPA). Pechini’s method was applied in the synthesis of CuO and MoO3. This procedure is advantageous because of its low cost, high yield, and simple operation, making it appropriate for large-scale synthesis. The oxides were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive (EDS), Fourier transform infrared (FTIR) and Raman spectroscopies. This synthesis provided pure and crystalline oxides and without the presence of impurities. XRD and Raman results for CuO indicated that the particles are monoclinic (crystalline) and the micrograph revealed uniformity in the particle size distribution and shape and a flake-like morphology. Cyclic voltammetry (CV) and square-wave voltammetry (SWV) demonstrated that the CuO-modified carbon paste electrode (CuO/CPE) displayed much higher electrocatalytic activity in relation to the anodic current in the E2 oxidation reaction than the CPE without modification, exhibiting a low detection limit of 0.021 μmol L−1 with a wide linear range from 0.06 to 0.80 μmol L−1. The developed method was applied to determine E2 in human urine and buttermilk samples. MoO3 was calcined in a muffle furnace at 500 and 600 °C. DRX and Raman results indicated that the obtained α-MoO3 microparticles were high pure and good crystallinity of orthorhombic-phase MoO3 crystal. It was observed that oxide tends to form powders which hads belt-like morphology. CV was used to obtain qualitative data and SWV was used for the analytical procedures. From these techniques, related the oxidation of the BPA was obtained, which increased linearly with the BPA concentration in the range of 0.03 to 1.6 μmol L-1. The limit of detection were 0.017 μmol L-1 and the developed sensor was applied to determinate directly BPA in real plastic samples. The proposed electrochemical sensors with CuO and MoO3 offers high repeatability, stability, fast response, low cost, and potential for practical application in the quantification of these endocrine disrupters.